2019
DOI: 10.1002/nml.21381
|View full text |Cite
|
Sign up to set email alerts
|

Tuning into performance and satisfaction in nonprofit orchestras: One link between transformational leadership and satisfaction is through reduction in conflict

Abstract: In this study, we tested hypotheses concerning volunteers' not‐for‐profit work, specifically the relations of transformational leadership with performance and satisfaction as well as the question of how task and relationship conflict fit into these relations. We argue that conflicts are detrimental to satisfaction and performance and that the frequency of conflict can be reduced through transformational leadership. We analyzed data from a large sample of lay orchestra musicians (N = 1,535) and found that music… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 48 publications
(92 reference statements)
1
3
0
1
Order By: Relevance
“…Previous research studies show the positive linkage of transformational leadership and performance (e.g. Kammerhoff et al, 2019;Sheehan et al, 2020). The result therefore highlights the importance of transformational leadership to support volunteers.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Previous research studies show the positive linkage of transformational leadership and performance (e.g. Kammerhoff et al, 2019;Sheehan et al, 2020). The result therefore highlights the importance of transformational leadership to support volunteers.…”
Section: Discussionsupporting
confidence: 52%
“…Transformational leaders effect change by building individuals' confidence and empowering them to perform their work tasks. Accumulated findings found that transformational leadership significantly affects individuals' motivation and performance (Gao et al, 2020;Kammerhoff et al, 2019;Waldman et al, 2001). Transformational leadership has posted a positive sign on individuals' job satisfaction, innovation, motivation and performance (e.g.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Previous research has examined the efficacy of different leadership models observed in NPOs. For example, Kammerhoff et al (2019) examined the impact of transformational leadership on employee performance in NPOs, and Javed et al (2019) examined the impact of inclusive leadership on employee empowerment and innovative behaviour. Cerne et al's (2013) research in the private sector found that authentic leadership behaviour was associated with increased creativity, and Grošelj et al (2021) found that authentic leadership behaviours promoted increased levels of empowerment, which is essential for facilitating a supportive environment.…”
Section: Authentic Leadershipmentioning
confidence: 99%
“…For example, Kammerhoff et al. (2019) examined the impact of transformational leadership on employee performance in NPOs, and Javed et al. (2019) examined the impact of inclusive leadership on employee empowerment and innovative behaviour.…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
“…Apesar de se caracterizarem como uma decorrência natural das relações humanas, os conflitos merecem atenção (O'Neill & McLarnon, 2017), pois podem produzir tensão e prejuízos para a saúde dos funcionários, atraso nos processos de tomada de decisão, insatisfação no trabalho, esgotamento emocional, aumento nos índices de rotatividade, além de colocar em risco as ações voltadas para o desenvolvimento dos profissionais e da organização (Kammerhoff, Lauenstein, & Schütz, 2019;Martins, Abad, & Peiró, 2014;Way, Jimmieson, & Bordia, 2019;Ye, Liu, & Gu, 2019).…”
Section: Introductionunclassified